Effect of Rotational Speed on Mechanical Properties and Microstructure Due to the Addition of Reinforcements on Friction Stir Welded Dissimilar Aluminum Alloys - Reddy, Baridula Ravinder; Abdullah, Ibrahim; C. K. M., Faizal; Ramaraju, Ramgopal Varma (Universiti Malaysia Pahang, 2016)
The Friction Stir Welding is a solid state joining process, which has many advantages in welding similar and dissimilar aluminium alloys when compared with the traditional fusion welding process. In the present investigation dissimilar aluminium alloys AA5052 and AA6063 were joined by friction stir welding by inserting Cu nanoparticles as reinforcements to study the effect of the same. Butt joints were obtained in 6mm thick plates with a longitudinal speed of 200mm/min, and at a load of 1.5kN with a rotational speed of 1200 and 1400 rpm. In order to determine the effect of process parameters due to the addition of Cu nanoparticles on microstructure and mechanical properties in dissimilar aluminium alloys was investigated. The result shows that due to the addition of reinforcements, the mechanical properties were improved, as the process parameters are changed. This behaviour was further supported by Electron dispersive X-ray analysis (EDX) studies, which provides elemental identification and quantitative compositional information.